To Be an Autoethnographer or Not to Be—That Is the Question - Marciniak, Lukasz (Qualitative Sociology Review, 2022)
It is the most personal article I have ever written, revealing my fears, hesitations, reflections, and decisions. I am still striving to write a scientific and academic paper, still looking for that academic framework that would allow this article to be recognized as a scientific text, with the reflection on that internal pressure and need to make it scientific. This is an article about the process of becoming an autoethnographer, creating a tool, shaping identity and research strategy, and becoming one.